Estimating From the Payer Perspective the Implementation Cost of Dating Matters®: A Comprehensive Teen Dating Violence Prevention Model - Luo, Feijun (Journal of interpersonal violence, 2022)
?Dating Matters?? is a CDC-developed comprehensive, multi-component teen dating violence (TDV) prevention model, made available to the public in 2019. A longitudinal, multi-site demonstration project found that the model significantly reduced TDV during middle school relative to an evidence-based, single-program intervention (Safe Dates; Niolon et al., 2019), when implemented across 46 middle schools in four high-risk urban areas with predominantly Black (55%) and Hispanic (28%) youth participants. Research on the costs of implementing TDV prevention strategies is limited, despite recognition within the field of prevention science that such data are critical to widespread dissemination. The current study adds to the available literature on the cost of dating violence prevention by estimating the budgetary impact from the payer perspective of implementing the comprehensive Dating Matters model, compared to Safe Dates, at four sites over four school years to inform prevention planning in communities. Total costs of implementing Dating Matters were relatively stable within sites over time but varied greatly between sites (M = $175,452 per year; range = $130,149 to $227,604). The mean per-student cost of Dating Matters was $145.40 but also ranged widely ($20.66 to $324.65) across sites and years. Variation was largely driven by staffing costs and number of students served. As expected, total and per-student costs were substantially lower at all sites for the Safe Dates program (M = $12,148; range = $2,848 to $17,840; $44.81 per student) compared to Dating Matters. This study provides an estimate from the payer perspective to demonstrate the budgetary impact of Dating Matters. These estimates can help inform implementation decisions and planning by potential funders, communities, and organizations as they seek to support and implement effective TDV prevention strategies. It also adds substantially to understanding of the additional costs associated with a move from single-program interventions to community-wide initiatives.